Blink [compact disc, unabridged] : the power of thinking without thinking - Gladwell, Malcolm, 1963- (Time Warner AudioBooks, 2005)
Utilizing case studies as diverse as speed dating, pop music, and the shooting of Amadou Diallo, Gladwell reveals that what we think of as decisions made in the blink of an eye are much more complicated than assumed. Drawing on cutting-edge neuroscience and psychology, he shows how the difference between good decision-making and bad has nothing to do with how much information we can process quickly, but on the few particular details on which we focus.